ANALISIS MARKET BASKET PADA MINIMARKET MENGGUNAKAN ALGORITMA APRIORI - Lase, Hellina Ofnani; Harman, Rika (Computer Science and Industrial Engineering, 2022)
ABSTRACT The advancement in science and technology has risen and changing people's lifestyles to be fast-paced and practical. Payment utilizing cashier machine and computerized systems are highly useful which is far easier for owners to record transactions, Hokagata Minimarket is one of the minimarkets employing a computerized system for transaction process. The purpose of this study is to determine client purchasing trends in order to guide business owners in planning product layouts. In this study, the authors collect transaction data, select the data at random, make data tabulations, sort the data by determining a minimum support value of 17 percent and a confidence level of 60 percent, and then manage the data using the association method to determine the relationship between frequently occurring data. Excel and Tanagra are utilized for data processing in this study. Alcohol, cigarettes, and kitchen spices had the greatest support value of 27.86 percent and confidence value of 68 percent following the testing technique. A priori application of sales transaction data is particularly advantageous and efficient in the process of constructing product combinations. With the application of this method, the product layout is more selective, and the acquisition of goods is contingent upon comprehension of the outcomes of system testing.